The Role of Transformational Leadership in Increasing Millennial Employee Engagement and Motivation - Susri,S., M. Erlin (Penelitian dan Pengembangan Ilmu, 2024)
Digital transformation and hybrid work models have changed organizational dynamics, especially in terms of employee engagement. Transformational leadership (TL) is becoming increasingly important to increase employee motivation and participation, especially among millennials who have a tendency towards digital flexibility and engagement. In this context, leaders need to adapt their communication styles by leveraging digital tools, such as video conferencing and collaboration platforms, to ensure team connectedness even if they are geographically separated. Additionally, employee autonomy should be promoted through flexible work arrangements, balanced with regular feedback and recognition. Investment in leadership training that focuses on digital skills and adaptive managerial capabilities is also urgently needed to overcome the challenges of a remote work environment. This research emphasizes the importance of leveraging technology as a facilitator of engagement and collaboration, and underscores the need to build an organizational culture that supports innovation and participative leadership. In this way, organizations can maintain the motivation and performance of millennial employees amidst changes in the ever-evolving work landscape.